دراسة السلوكية الوراثية لبعض صفات الغلة في هجن نصف تبادلية من الذرة الصفراء ( Zea mays L. ) - مسعود, إيمان; خوري, بولص; قبيلي, صالح (Latakia University Journal -Biological Sciences Series, 2014)
نفِّذ التهجين نصف التبادلي بين ست سلالات مرباة ذاتيّاً، في قسم بحوث الذرة التابع للهيئة العامّة للبحوث العلميّة الزراعيّة بدمشق، في الموسمين الزراعيين 2010- 2011، بهدف تقدير القدرة العامة والخاصة على التوافق وكذلك قوّة الهجين لصفات: عدد الصفوف بالعرنوس (صف), وعدد الحبوب بالصف (حبة), وطول وقطر العرنوس (سم)، ووزن 100حبة (غ)، والغلة الحبية (طن/هكتار). وخلصت النتائج إلى ما يلي: كان تباين السلالات والهجن عالي المعنوية لكلِّ الصفات المدروسة، دلالة على التباعد الوراثي بين السلالات الأبوية. أظهرت القدرة العامة والخاصة على التوافق تبايناً عالي المعنوية في كلّ الصفات، ما يوضح مساهمة كلٍّ من الفعل الوراثي التراكمي واللاتراكمي في توريث هذه الصفات كافةً. بينت نسبة تباين القدرة العامة إلى تباين القدرة الخاصة σ2GCA/σ2SCAسيطرة الفعل الوراثي التراكمي على وراثة جميع الصفات المدروسة، ماعدا صفتي وزن 100حبة والغلة الحبية اللتان سيطر عليهما الفعل الوراثي اللاتراكمي. أظهرت جميع الهجن قوّة هجين إيجابية عالية المعنوية قياساً إلى متوسط وأفضل الأبوين لجميع الصفات المدروسة. أبدت السلالات (CML.317)، (CML.371)، (CML.373)، (CML.367)، قدرة عامة موجبة وعالية المعنوية على التوافق في صفة الغلة الحبية. أظهرت سبعة هجن قدرة خاصة جيدة على التوافق في صفة الغلة الحبية كان أفضلها الهجين (CML.317×CML.371). A half diallel set of crosses among six inbred lines of maize were evaluated at the Maize Research Department (G.C.S.A.R.) in Damascus Governorate during 2010 and 2011 growing seasons to estimate heterosis and combining ability components for the number of rows per ear, number of kernels per ear, ear length (cm), ear diameter(cm), 100-kernel weight (g), and grain yield (ton /hec). The inbred lines, crosses, general combining ability (GCA) and specific combining ability (SCA) mean squares were highly significant for all the studied traits, showing the existence of a genetic variance among lines. The ratios of GCA to SCA detected for the studied traits showed the dominance of an additive gene action for all the studied traits except for 100-kernel weight and grain yield which showed the predominance of a non-additive gene action. The heterosis percentage for the studied traits was significant based on mid and better parents. The GCA effects showed that the lines CML.317, CML.371, CML.373 and CML.367 were good general combiners for grain yield, while the SCA effects showed that seven hybrids were the best F1 cross combinations such as (CML.317×CML.371) for grain yield.